Manajemen Bimbingan Prestasi Religi di Sekolah Dasar - Rosyid, Ahmad; Suswandari, Meidawati; Srimulyati, Srimulyati; Prafitasari, Ferrinda; Elita, Mutiara Dana; Subekti, Anjas Asma (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to explore how the program fosters students' religious values and contributes to their academic and non-academic developmental achievements. The method used is descriptive and qualitative. Data were collected through observations of program implementation and interviews involving three informants: a Principal, an Islamic Religious Teacher, and one student. Furthermore, documentation was also conducted to supplement the necessary information through related documents. Based on the analysis of the collected data, it can be concluded that the management stages, from planning to evaluation, have been implemented through a structured hierarchical system, resulting in students who excel in religious competitions. The management of Religious Achievement Guidance implemented by SD Negeri 3 Sidoharjo has undergone stages from planning to evaluation and has a structured hierarchy of accountability. The program implemented and developed aligns with the objectives formulated during the planning process. In addition, the school also involves religious leaders to maintain the quality of guidance and produce students who excel in religious competitions. Thus, this study provides insights into how to establish religious guidance in public schools to attract the interest of parents who emphasize religious education and habits from an early age. To explore the research on religious guidance management in more depth, further research is suggested to expand the research objects and provide a more adaptive management picture across various school conditions. (Palatino Linotype 11, Justify).